How Contemporary Can Tradition Be?: A Case Study of the Kesra Village Museum, Tunisia. Issue 1 (21st June 2016) - Hamzaoui, Sonia M'Layah
Abstract: Although Kesra is one of the top five archaeological Berber villages in Tunisia – the likely cradle of Numidian, Punic, Roman and Byzantine civilizations, it is, to date, the object of only minor scholarly interest. The Byzantine fortress and current houses show the continual occupation of the site throughout time. The people of Kesra are traditional, and very much attached to ancestral values. Their heritage is deep‐rooted and bears witness to their beliefs, customs and traditions. This article explores the tensions between contemporaneity and tradition through an overview of the Kesra museum project. The main problem at hand was to decide on the nature and purpose of this small‐village museum, by contrasting wealth with poverty and tradition with modernity. The realisation of that dichotomy aimed to educate visitors on the villagers' contrasting experiences by presenting a narrative made of oppositions, which are illustrated in the museum's architectural design and its scientific, museographical and scenographical programmes.